2013
DOI: 10.1111/cobi.12152
|View full text |Cite
|
Sign up to set email alerts
|

Trophic Cascades Following the Disease‐Induced Decline of an Apex Predator, the Tasmanian Devil

Abstract: As apex predators disappear worldwide, there is escalating evidence of their importance in maintaining the integrity and diversity of the ecosystems they inhabit. The largest extant marsupial carnivore, the Tasmanian devil (Sarcophilus harrisii) is threatened with extinction from a transmissible cancer, devil facial tumor disease (DFTD). The disease, first observed in 1996, has led to apparent population declines in excess of 95% in some areas and has spread to more than 80% of their range. We analyzed a long-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
127
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 104 publications
(135 citation statements)
references
References 37 publications
7
127
1
Order By: Relevance
“…Future research should include tumour lineage dynamics within an evolutionary epidemiological analytical framework, as well as assessing variation in host tolerance to different DFTD genetic variants under different ecological or immunological conditions. Transmissible clonal cancers in wildlife have only recently been recognized as a threat to biodiversity conservation [12,43], including both direct effects on species decline and the trophic cascades that result from the loss of keystone species and ecological functions, such as is occurring in Tasmania with the severe decline of its top mammalian predator [44]. The Tasmanian devil's facial tumour disease is a new transmissible cancer that we have studied in the wild almost since its emergence.…”
Section: Discussionmentioning
confidence: 99%
“…Future research should include tumour lineage dynamics within an evolutionary epidemiological analytical framework, as well as assessing variation in host tolerance to different DFTD genetic variants under different ecological or immunological conditions. Transmissible clonal cancers in wildlife have only recently been recognized as a threat to biodiversity conservation [12,43], including both direct effects on species decline and the trophic cascades that result from the loss of keystone species and ecological functions, such as is occurring in Tasmania with the severe decline of its top mammalian predator [44]. The Tasmanian devil's facial tumour disease is a new transmissible cancer that we have studied in the wild almost since its emergence.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in California declines in coyote populations led to increases in native (skunks, racoons, foxes) and exotic (feral cats, opossums) meso-predators causing local extinctions of scrub-feeding birds (Crooks and Soule 1999). Similar interactions have occurred for Tasmanian devils and quolls in Australia, following the near extinction of Tasmanian devils due to a disease outbreak (Hollings et al 2014). In this study, we found evidence to suggest that predator/mesopredator interactions occurred at the Palm Islands between large fisheries-targeted predators such as coral trout and snappers, and smaller non-target meso-predators such as small groupers and cods.…”
Section: Predictions 1 and 2: Predator-prey Interactions And Prey Relmentioning
confidence: 93%
“…B 282: 20150124 similar (0.4-0.6/10 km) in each of three regions we studied [19]. Numbers declined dramatically following disease arrival, but no such decline was evident in the disease-free northwest [19]. The higher levels of terrestrial activity of possums in areas with lower predation risk, evident from the hair-trap surveys and the earlier detection of food patches, may represent an increase in ground-foraging behaviour (microhabitat use), changes in vegetation use (macrohabitat use), greater population abundance or combinations of all three.…”
Section: Discussionmentioning
confidence: 88%